2020
DOI: 10.3389/fcell.2020.00694
|View full text |Cite
|
Sign up to set email alerts
|

Autologous Fractionated Adipose Tissue as a Natural Biomaterial and Novel One-Step Stem Cell Therapy for Repairing Articular Cartilage Defects

Abstract: Articular cartilage damage remains a tough challenge for clinicians. Stem cells have emerged promising biologics in regenerative medicine. Previous research has widely demonstrated that adipose-derived mesenchymal stem cells (ADSCs) can promote cartilage repair due to their multipotency. However, enzymatic isolation and monolayer expansion of ADSCs decrease their differentiation potential and limit their clinical application. Here, a novel adipose tissue-derived product, extracellular matrix/stromal vascular f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 44 publications
0
14
0
Order By: Relevance
“…Recently, a strategy was proposed to simplify the cell therapy procedure and remove steps associated with the enzymatic isolation, cell expansion and scaffold fabrication. Autologous fractionated adipose tissue (so-called ECM/SVF-gel in the study), a gel-like substance consisting of adipose tissues mechanically destroyed by simple mechanical shifting between two syringes, was applied to cartilage injury repair in combination with a microfracture in a rabbit model [ 134 ]. Twelve weeks after the ECM/SVF-gel injection, the knee joints were evaluated using MRI, macroscopic observation, histology and IHC.…”
Section: Adipose-derived Stem Cellsmentioning
confidence: 99%
“…Recently, a strategy was proposed to simplify the cell therapy procedure and remove steps associated with the enzymatic isolation, cell expansion and scaffold fabrication. Autologous fractionated adipose tissue (so-called ECM/SVF-gel in the study), a gel-like substance consisting of adipose tissues mechanically destroyed by simple mechanical shifting between two syringes, was applied to cartilage injury repair in combination with a microfracture in a rabbit model [ 134 ]. Twelve weeks after the ECM/SVF-gel injection, the knee joints were evaluated using MRI, macroscopic observation, histology and IHC.…”
Section: Adipose-derived Stem Cellsmentioning
confidence: 99%
“…Another study by Pers and others demonstrated that patients who received autologous ASCs injections in the knee showed improvement due to the paracrine factors released from the cells inducing an anti-inflammatory response ( Pers et al, 2018 ). A recent study conducted by Li and others described the use of ECM/SVF-gel fraction in cartilage defect repair as ASCs migrate from the gel and differentiate in a natural microenvironment, thus increasing the therapeutic potential of ASCs ( Li et al, 2020 ). Furthermore, engineered cartilage is another area that is gaining interest, as ASCs and Poly ε-Caprolactone Scaffolds have successfully been used to regenerate cartilage in vitro for later transplantation into a mouse model ( Nguyen and Vu, 2021 ).…”
Section: Current Therapeutic Applications Of Ascsmentioning
confidence: 99%
“…Nonetheless, this study has provided insight into the role of ASCs in ITP. ASCs are easily attached to plastic culture bottles and expanded in vitro [63]. These cells can also differentiate into multiple cell lines and thus have the potential to repair, maintain, or strengthen various tissues.…”
Section: Ascs In Itpmentioning
confidence: 99%